Addiction Treatment Clients' Reactions to Graphic Warning Labels on Cigarette Packs. (July 2017) - Pagano, Anna; Gubner, Noah; Tajima, Barbara; Yip, Deborah; Henderson, Catherine; Guydish, Joseph
Graphic warning labels (GWLs) on cigarette packs have been tested among diverse groups at high risk for tobacco use. However, little is known about the effectiveness of GWL interventions for persons with substance use disorders, whose smoking prevalence is 3 to 4 times that of the general population. After a experimental study which exposed clients in residential addiction treatment to GWLs for 30 days, we conducted five focus groups with trial participants ( N = 33) to explore how exposure to the labels may have impacted their readiness to quit smoking. Focus group interviews were analyzed thematically. Interviewees reported that GWLs were more effective than text-based warnings for increasing quit intentions due to greater cognitive and emotional impact. Male and female interviewees expressed gender-specific reactions to the labels. Addiction treatment programs are a strategic site for GWL and other tobacco interventions due to the tobacco-vulnerable populations they serve.